Causal effect of iron status on lung function: A Mendelian randomization study - Yu, Zhimin; Xu, Chengkai; Fang, Chenggang; Zhang, Fangfang (Frontiers in Nutrition, 2022)
Background: The association between systemic iron status and lung function was conflicting in observational studies. We aim to explore the potential causal relationships between iron status and the levels of lung function using the two-sample Mendelian randomization (MR) design. Methods: Genetic instruments associated with iron status biomarkers were retrieved from the Genetics of Iron Status (GIS) consortium (N=48,972). Summary statistics of these genetic instruments with lung function were extracted from a meta-analysis of UK Biobank and SpiroMeta consortium (N=400,102). The main analyses were performed using the inverse-variance weighted method, and complemented by multiple sensitivity analyses. Results: Based on conservative genetic instruments, MR analyses showed that genetically predicted higher iron (beta: 0.036 per 1 SD increase, 95% confidence interval (CI): 0.016 to 0.056, P = 3.51×10-4), log10-transformed ferritin (beta: 0.081, 95% CI: 0.047 to 0.116, P = 4.11×10-6), and transferrin saturation (beta: 0.027, 95% CI: 0.015 to 0.038, P = 1.09×10-5) were associated with increased forced expiratory volume in 1 second (FEV1), whereas higher transferrin was associated with decreased FEV1 (beta: -0.036, 95% CI: -0.064 to -0.008, P = 0.01). A significant positive association between iron status and forced vital capacity (FVC) was also observed. However, there is no causal association between iron status and FEV1-to-FVC ratio (P = 0.10). Similar results were obtained from the liberal instruments analyses and multiple sensitivity analyses. Conclusions: Our study provided strong evidence to support that higher iron status is causally associated with higher levels of FEV1 and FVC, but has no impact on airway obstruction, confirming iron status as an important target for lung function management.